2017
DOI: 10.15406/aowmc.2017.07.00195
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Weight Gain and Obesity: An Opportunity for Dietary Management after Successful Kidney Transplantation

Abstract: Several factors contributing to post-transplant weight gain and obesity may occur during pre-, peri-, and/or post-transplant periods. The main factors are summarized in Figure 1. Pre-transplant periodDuring the pre-transplant period, there are several factors related to advanced CKD and ESRD that potentially increase the risk for post-transplant weight gain and obesity. These main risk factors include:Pre-transplant obesity: Data from a single kidney transplant center revealed that around one-third of ESRD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Furthermore, the number of RTRs meeting the 70% DRI recommendation for vitamins A, C, and B12 and iron decreased within the 5-year period. This trend might be associated with the RTRs continuing a dietary pattern from their dialysis days [ 33 ], resulting in low consumption of dairy products, dark green vegetables, nuts, and other foods rich in these vitamins and minerals. Cianciolo et al suggested that the insufficient intake of folic acid and vitamin B12 in patients with CKD resulted in an elevated blood homocysteine level, potentially increasing the risks of CVD and CKD progression [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of RTRs meeting the 70% DRI recommendation for vitamins A, C, and B12 and iron decreased within the 5-year period. This trend might be associated with the RTRs continuing a dietary pattern from their dialysis days [ 33 ], resulting in low consumption of dairy products, dark green vegetables, nuts, and other foods rich in these vitamins and minerals. Cianciolo et al suggested that the insufficient intake of folic acid and vitamin B12 in patients with CKD resulted in an elevated blood homocysteine level, potentially increasing the risks of CVD and CKD progression [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation science between additional research with strong evidence and clinical practice should assist to close to knowledge-practice gap to improve transplant outcomes by dietary interventions. complications such as obesity [14,15]. We focus our review on macronutrients and dietary patterns.…”
Section: Key Pointsmentioning
confidence: 99%
“…Appropriate dietary management posttransplant needs to be modified by period posttransplant to improve allograft outcomes and avoid complications such as obesity [14,15]. We focus our review on macronutrients and dietary patterns.…”
Section: Pathogenesis Of Kidney Allograft Loss: Opportunities To Prol...mentioning
confidence: 99%